Interleukin-11-expressing fibroblasts have a unique gene signature correlated with poor prognosis of colorectal cancer - Takashi Nishina (Nature Portfolio, 2021)
The stromal fibroblast population in the colon is composed of heterogeneous and distinct cell subtypes that play a crucial role in the development of colitis and colon cancer. Here the authors generate IL-11 reporter mice and characterize the origin and phenotype of inflammatory IL-11+ fibroblasts in colitis and colon cancer preclinical models.